Estimasi Emisi Kendaraan Bermotor untuk Memprediksi Beban Pencemar Udara CO dan NOx di Tempat Pelelangan Ikan Kota Kendari - Arisman, Arisman; Rosdiana, Rosdiana; Adami, Aryani (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2023)
Transportation has a positive impact in supporting community activities and helps determine regional development through the distribution of goods and services, besides that it also has a negative impact on the environment, especially air quality in urban areas. Fish Auction Place is a place that is usually located in a port or fish landing base and in that place, there is a sale of fish and marine products either by auction or not. This study aims to observe the prediction of motor vehicle emission load by using analytical prediction studies and simple statistical data about the possible estimates of vehicle emissions produced by motorized vehicles at the Kendari City Fish Auction Place. Based on the results of the study, the volume of vehicle traffic passing at the Kendari City Fish Auction Place was 1,774 vehicles/hour, 8,517 vehicles/day, and 3,100,664 vehicles/year. The type of motorcycle vehicle is the vehicle that passes the most while the bus is the vehicle that passes the least at the research location. It is known that the largest CO emission load is produced by motorcycle vehicles, which is 3.8981 tons/year, and the smallest is produced by buses at 0.0011 tons/year. While the largest NOx emission load is generated by diesel-fueled cars, which is 0.1369 tons/year and the smallest is generated by bus vehicles, which is 0.0012 tons/year.